Vermistella arctica n. sp. Nominates the Genus Vermistella as a Candidate for Taxon with Bipolar Distribution - Tyml, Tomáš; Kostka, Martin; Ditrich, Oleg; Dyková, Iva (The Journal of eukaryotic microbiology, 2016)
A new amoebozoan species, Vermistella arctica n. sp., is described from marine habitats in the central part of Svalbard archipelago. This is the first report on Arctic amoebae belonging to the genus Vermistella Moran and Anderson, 2007, the type species of which was described from the opposite pole of the planet. Psychrophily proved in the new strains qualifies the genus Vermistella as a bipolar taxon. Molecular phylogenetic analyses based on 18S rDNA and actin sequences did not show any affinity of the genus Vermistella to Stygamoeba regulata ATCC(®) 50892(™) strain. A close phylogenetic relationship was found between Vermistella spp. and a sequence originating from an environmental sample from Cariaco basin, the largest marine permanently anoxic system in the world. Possible mechanisms of bipolar distribution are discussed.
Keywords: fylogeografie; RNA, Ribosomal, 16S; Cold Climate; Arktida; Actins; Arctic Regions; Phylogeography; Lobosea; aktiny; free-living amoebae; transmisní elektronová mikroskopie; Svalbard; DNA, Ribosomal; bipolar distribution; SSU; Amoebozoa; protozoální DNA; Amoeba; RNA ribozomální 16S; mořská voda; Seawater; fylogeneze; Microscopy, Electron, Transmission; ribozomální DNA; actin; polar regions; phylogeny; DNA, Protozoan; biogeography; Phylogeny; studené klima